Bacillus cereus Isolated From Vegetables in China: Incidence, Genetic Diversity, Virulence Genes, and Antimicrobial Resistance - Yu, Pengfei; Yu, Shubo; Wang, Juan; Guo, Hui; Zhang, Ying; Liao, Xiyu; Zhang, Junhui; Wu, Shi; Gu, Qihui; Xue, Liang; Zeng, Haiyan; Pang, Rui; et al. (Frontiers in Microbiology, 2019)
Bacillus cereus is a common food-borne pathogen that can induce diarrheal and emetic symptoms. Due to its widely distribution in different environments, B. cereus can be found in various food including fresh vegetables. As been growing popular all over the world, the risk of bacterial contamination in fresh vegetables should be fully evaluated when considering that vegetables are not commonly sterilized by heat treatment. It is therefore of paramount importance to perform risk assessment of B. cereus in vegetables. In this study, we isolated 294 B. cereus from vegetable samples in different regions of China, and evaluated the contamination level, existence of virulence genes, antibiotic resistance profile and genetic polymorphism of these isolates. B. cereus was found in 268 vegetable samples and the average contamination level was 136 MPN/g. The distribution of virulence gene was accessed towards 8 enterotoxigenic genes (hblA, hblC, hblD, nheA, nheB, nheC, cytK and bceT) and one emetic gene (cesB). Eighty two percent of the strains harbored enterotoxigenic genes hblACD and 95% isolates contained nheABC gene cluster. The detection rate of cytK, bceT and cesB genes were 87%, 62% and 3%, respectively. Antibiotic susceptibility assessment revealed that most of the isolates were resistant to β-lactam antibiotics and rifampicin, but susceptible to other antibiotics such as imipenem, gentamicin, kanamycin and so on. In addition, more than 95.6% of the isolates displayed resistance to three or more antibiotics. Genetic diversity analysis by multi-locus sequence typing indicated that all 294 isolates were classified into 210 different sequence types (STs), of which 145 isolates were identified to be 137 new STs. The most prevalent ST was B. cereus ST770 but only contained eight isolates, indicating high genetic diversity of B. cereus isolates in vegetables. In conclusion, our research provides the first reference on the prevalence, contamination level and characteristics of B. cereus isolated from vegetables collected all over China, suggesting a potential high risk of B. cereus when consuming vegetables without proper handling.